Knowledge, attitude and practices of reproductive health among early married women of urban slums of Lucknow, Uttar Pradesh. - Tripathi, Priyanka; Singh, Neetu (International Journal of Psychosocial Rehabilitation, 2020)
Background: Previous research shows that the women who are married before legal age , living in poor communities, and belonging to the age group 15 to 24 years face more reproductive health problems due to a lack of sufficient knowledge. Objective: To know about the socio-demographic profile of the target population. To assess knowledge, attitude, and practice level regarding reproductive health and the association between knowledge, attitude, and practice scores of the women who are living in the urban slums of Lucknow. Method: A cross-sectional study was conducted among 253 early married women of the age of 15-24 years in the slums of the Lucknow district. Results: Out of 253 respondents the majority of the respondents 211 (83.4%), belonged to the 21-24 years age group; 230 (90.9%) were married at the age between 15-17 years; 169 (66.8%) Hindu; 122 (48.2%) OBC; 114 (45.1%) illiterate; 208 (82.2%) were homemakers; nuclear family 158 (62.5%) and 146 (57.7%) were living on rent in the semi-pacca house, 117 (46.2%). The majority of the respondents, 119 (47%), belonged to the III class. The majority of the women had a low level of knowledge (91.7 %), a negative attitude (79.1%), and poor practice (81.8%). There is an association between the score of knowledge and attitude (r=0.708, p<.01), knowledge and practice (r=0.616, p<.01), and attitude score is associated with practice score (r=0.480, p<.01). Conclusion: There is a low level of knowledge, attitude, and practice of reproductive health among the study subjects.